2012
DOI: 10.1093/nar/gks294
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of chemo-sensitizing siRNAs to HER2+-breast cancer cells using RNA aptamers

Abstract: Human epidermal growth factor receptor 2 (HER2) expression in breast cancer is associated with an aggressive phenotype and poor prognosis, making it an appealing therapeutic target. Trastuzumab, an HER2 antibody-based inhibitor, is currently the leading targeted treatment for HER2+-breast cancers. Unfortunately, many patients inevitably develop resistance to the therapy, highlighting the need for alternative targeted therapeutic options. In this study, we used a novel, cell-based selection approach for isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
189
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(191 citation statements)
references
References 107 publications
(106 reference statements)
1
189
0
1
Order By: Relevance
“…This is well correlated with previously reported studies. 58,59 In the HPLC quantification of DOCT from the MKN-28 cancer-bearing mice, a time-dependent reduction in plasma concentration of DOCT was observed, indicating eventual clearance of the Nps or the released DOCT from the circulation following the hepatic or renal route as indicated by liver and kidney accumulation, respectively. Studies have reported that even PEG modification could not enhance the circulation time, and that the Nps were cleared by the RES system following liver and spleen accumulation.…”
mentioning
confidence: 99%
“…This is well correlated with previously reported studies. 58,59 In the HPLC quantification of DOCT from the MKN-28 cancer-bearing mice, a time-dependent reduction in plasma concentration of DOCT was observed, indicating eventual clearance of the Nps or the released DOCT from the circulation following the hepatic or renal route as indicated by liver and kidney accumulation, respectively. Studies have reported that even PEG modification could not enhance the circulation time, and that the Nps were cleared by the RES system following liver and spleen accumulation.…”
mentioning
confidence: 99%
“…We deliver siRNAs into epithelial cancer cells by linking them to an RNA aptamer that binds to EpCAM, the first described tumor antigen, a cell surface receptor overexpressed on epithelial cancers, including basal-like TNBCs. Aptamer-linked siRNAs, known as aptamer-siRNA chimeras (AsiC), have been used in small animal models to treat prostate cancer and prevent HIV infection (10)(11)(12)(13)(14)(15)(16)(17)(18). We chose EpCAM for targeting basal-like TNBC because EpCAM is highly expressed on all epithelial cancers.…”
Section: Introductionmentioning
confidence: 99%
“…1) is time consuming, costly, and often fails to identify high-affinity aptamer due to PCR bias (PCR is used after each round to amplify the target bound aptamers). In several recent studies, highthroughput sequencing enabled the identification of high-affinity aptamers after many fewer rounds of selection, reducing time, cost, and PCR bias (12)(13)(14)(15). In the standard protocol, aptamers are selected against recombinant protein products in solution.…”
Section: Oligonucleotide Aptamer Ligandsmentioning
confidence: 99%